PENGARUH PENERAPAN SISTEM E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PEMAHAMAN INTERNET SEBAGAI VARIABEL PEMODERASI PADA KPP PRATAMA GARUT - Rustandi, Rustandi; Erfiansyah, Erfan (2021)
The purpose of this study was to test effect of the implementation of the e-Filling system on the Compliance of Personal Taxpayers with Internet Understanding as a Moderating Variable at KPP Pratama Garut. The sampling technique was carried out by accidental sampling technique. The population of this research is the individual taxpayers who are registered at KPP Pratama Garut and the respondents who are used as samples are 105 respondents. The data analysis method used is simple linear regression and Moderated Regression Analysis (MRA). The results showed that the implementation of the e-filling system on taxpayer compliance had a positive effect on understanding the internet affecting the application of the e-filling system on taxpayer compliance.